Implementasi Quick Response Code dan Filter Unsharp dalam Deteksi Objek untuk Pemindahan Benda dengan Integrasi Database SQL menggunakan Robot Manipulator - Refsi Ilham Cahya; Rizal Maulana; Hurriyatul Fitriyah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The increase in the number of E-commerce retail users is currently growing very rapidly coupled with the effects of the covid-19 outbreak which has made the number of users increase. Therefore, an automation system is needed to help support the improvement of the E-commerce business that can perform tasks efficiently without the need to increase production costs. This system will use the camera to identify objects with images but this image will have noise that affects the identification process. The results of taking pictures of the object will be processed by the Raspberry Pi4 with an Unsharp filter to eliminate noise, then the process of identifying information data from the QR code on the object and determining the initial coordinates of the object will be carried out. The results of this data will later be forwarded to OpenCM to move the manipulator robot using the Inverse Kinematics function. In addition, this system will also send information data to the database for data storage. The use of the Unsharp Filter and QR Code methods in this system produces an accuracy value of 100% with a computation time of 801 ms in 40 times of object reading testing. As for the inverse method, this system has an error of 9.12% to reach the coordinates in 10 times of testing. And to move an object the system requires a computation time of 11 seconds for each type of object for scanning, moving, and storing information from the object.